PENGATURAN SISTEM KEAMANAN TRANSAKSI PEMBAYARAN DENGAN DOMPET ELEKTRONIK(STUDI PERBANDINGAN ANTARA INDONESIA DAN SINGAPURA): Regulating The Security System of Payment Transactions with Electronic Wallet (A Comparative Study Between Indonesia and Singapore) - Mali, Yosefa Oktriviani Mutiara; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2025)
Advances in financial technology bring convenience and efficiency in electronic payment systems, one of which is the electronic wallet that is popular among people today. Electronic wallets are storage of payment instruments using cards or electronic money, holding funds and making payments. Behind the convenience of using electronic wallets, there are also frequent security problems, namely balance breaches, hacking of information data and illegal access to electronic wallet accounts in an application so that a comparison of electronic wallet security system arrangements in Indonesia and Singapore is carried out. The research was conducted normatively in the form of comparative law using secondary data sources, descriptive research nature, data analysis with qualitative methods, and deductive inference. In Indonesia, the regulation of electronic wallet security systems in several regulations and in Singapore is regulated in the Payment Service Act 2019 and its statutory guidelines. The results showed that there are 4 similarities and 6 differences in electronic wallet security arrangements seen from the aspects of licensing, cybersecurity, auditing, personal data protection, risk management, information system security, access control and anti-money laundering. With the similarities and differences in the arrangements, Indonesia can adopt the arrangements from Singapore to develop regulations for electronic wallet security systems to overcome growing technological crime.